Rare Occurrence of Herpes Zoster of Trigeminal Nerve following Extraction of Tooth - A. Winnifred Christy; T. Jones Raja Deva Thanmbi; J. Leelavathy; Antoinette Rhema Louis (Case Reports in Dentistry)
Herpes Zoster also known as Shingles is an acute viral infection which is an extremely painful and incapacitating ailment. It results from the reactivation of the varicella zoster virus. The triggering factors for the onset of an attack of Herpes Zoster include some form of immunosuppression. The diagnosis of Herpes Zoster can be made on proper medical history and a thorough clinical examination. Here is the report of a male patient affected by Herpes Zoster infection which followed after extraction of a lower first molar.